Kinetic study of copper(II)-and iron(III) -: Catalyzed oxidation of L-ascorbic acid in aspartame-containing aerated solution:: Protection of ascorbic acid - Imer, F.; Sonmezoglu, I.; Yildogan, B.; Kilic, H.; Apak, R. (CODON PUBLICATIONS, 2008)
The kinetics of uncatalyzed and metal-catalyzed oxidation of ascorbic acid (AA) in aerated aspartame solutions was studied at 0.1 ionic strength; AA was estimated with CUPRAC spectrophotometry. At fixed pH, the AA oxidation rate constants decreased with increasing aspartame content for a fixed Cu(II) concentration and increased with increasing Cu(II) or Fe(III) ratio for a fixed aspartame level. The stability of copper-aspartame complex inhibited the catalytic activity of copper in AA oxidation. Aspartame, with or without citrate, protected the AA from catalytic oxidation. The protective level of aspartame should be in excess of Cu(II), and close to the AA concentrations to prevent a prooxidative effect of AA.
Keywords: ascorbic acid; aspartame; catalyzed oxidation; Cu(II); Fe(III); food stability; VITAMIN-C; SPECTROPHOTOMETRIC DETERMINATION; MOLECULAR-OXYGEN; FREE-RADICALS; METAL-ION; COPPER(II)-NEOCUPROINE; PHARMACEUTICALS; STABILITY; COMPLEXES; CHEMISTRY; Food Science & Technology